Acoustic Signal Detection of Search-Phase Echolocation Bat Calls with CNN - M. R., Anala; R., Hemavathy; M., Dhanush (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Bats are one of the most diverse species on earth. Not only do they provide highly beneficial services to nature such as pollination and pest control, they provide useful insights on the changes occurring to the ecosystem as a result of anthropogenic change. Therefore, bat tracking helps in the conservation of endangered bat species and also to measure trends in biodiversity. Bats play a vital role in our ecosystem, however, they are least studied and marred with myths. Hence it is necessary to study and monitor their population dynamics to get an insight on roost size, mortality rate, migration pattern, breeding season, etc. Insectivorous bats use “Echolocation” to communicate with each other, to find roosts, to detect prey and obstacles while navigating in flight. This paper proposes a Convolution Neural Network (CNN) based pipeline for automatically detecting search-phase calls produced by echolocating bats in noisy, real-world recordings. Audio files are first converted into spectrogram or time-frequency representation and then denoised. The performance results of this model were compared with other existing models on different evaluation metrics like precision, recall, Receiver Operating Characteristic (ROC) curves, and Precision Recall (PR) curves. The model performed better than the existing systems on three different acoustic datasets. Around 500 more bat calls were detected across all 3 datasets compared to that of the existing systems, with a significant increase in recall of the proposed model, as high as 11%. The proposed detection system proved to be capable of detecting echolocation bat calls reliably.